2014
DOI: 10.3171/2014.4.jns13932
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of intraocular pressure measurement for the detection of raised intracranial pressure: meta-analysis

Abstract: Object Because clinical examination and imaging may be unreliable indicators of intracranial hypertension, intraocular pressure (IOP) measurement has been proposed as a noninvasive method of diagnosis. The authors conducted a systematic review and meta-analysis to determine the correlation between IOP and intracranial pressure (ICP) and the diagnostic accuracy of IOP measurement for detection of intracranial hypertension. Methods The authors searched bibliographic databases (Ovid MEDLINE, Ovid EMBASE, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Some investigators have argued that IOP is correlated with ICP (Lashutka et al, 2004;Li et al, 2012), but others argue that they are unrelated (Czarnik et al, 2009;Kirk et al, 2011). Still others have concluded that, although there is a correlation between ICP and IOP, IOP is a "poor predictor" of ICP (Golan et al, 2013;Spentzas et al, 2010;Yavin et al, 2014). Our study answers this question and shows that all authors are partially correct.…”
Section: Figure 4 Pressures Around the Optic Nerve (On)supporting
confidence: 59%
“…Some investigators have argued that IOP is correlated with ICP (Lashutka et al, 2004;Li et al, 2012), but others argue that they are unrelated (Czarnik et al, 2009;Kirk et al, 2011). Still others have concluded that, although there is a correlation between ICP and IOP, IOP is a "poor predictor" of ICP (Golan et al, 2013;Spentzas et al, 2010;Yavin et al, 2014). Our study answers this question and shows that all authors are partially correct.…”
Section: Figure 4 Pressures Around the Optic Nerve (On)supporting
confidence: 59%
“…These features included dilation of the optic nerve sheath, "bulging" of the terminal optic sheath subarachnoid space into the posterior aspect of the globe at the ONH, and a depressed perfusion of the optic disk/nerve junction. A positive correlation between ICP and IOP is found in some clinical studies, and hence, IOP is proposed as a noninvasive measure of ICP for clinical utility (214), but it seems to lack the accuracy necessary for close management of intracranial pressure in emergency medicine (267,306).…”
Section: Iop/icp Relationship In Healthy and Disease Statesmentioning
confidence: 99%
“…It has been reported that intrathoracic pressure, intracerebral pressure [ 4 , 5 ], and intraocular pressure [ 6 , 7 ] increase when IAP increases. Nevertheless, it is known that increased intracranial pressure would affect intraocular pressure [ 8 ]. However, there have not been adequate studies about the relationship between IAP and IOP.…”
Section: Introductionmentioning
confidence: 99%